Impact of Shellac and Gum Arabic in Shoe Polish Formulation based on Karanj Oil - Pandey, S. K.; Job, M.; Mishra, P. K.; Pandey, S. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted from August, 2021 to March, 2022 at the Department of Agricultural Engineering, Birsa Agricultural University, Kanke, Ranchi, Jharkhand, India to develop shoe polish based on Karanj oil and the impact of shellac and gum arabic in its formulation. The standardized composition of shoe polish was obtained as 3 part oil and one-part bee wax containing other elements like colour pigment, shellac, gum arabic and turpentine oil. To overcome the problem of colour, sixteen various combinations of shellac and gum arabic were carried out for improvement of colour in each case of black and brown polish. The developed shoe polish was tested for texture, applicability, spreadability, and ease in taking out the material. Colour was recorded with a gloss meter. The highest gloss meter reading i.e. 10.62 GU was recorded in the case of a black shoe polish containing shellac and gum arabic each weighing 0.75 g whereas a sample containing 1.25 g shellac and gum arabic each showed the lowest gloss reading of 3.88 GU. In the case of brown polish, the highest gloss meter reading i.e. 5.24 GU was recorded in the case of a sample containing shellac and gum arabic weighing 1.25 g each, and the lowest was observed in the case of the sample containing shellac weighing 0.5g and gum arabic weighing 0.75 g. Based on gloss value and sensory evaluation, the developed sample was found very near to standard brand shoe polish (Cherry) except that it gave an oily appearance initially.